The Concept and Practice of Balanced Human Education in Ibnu Miskawaih: An Analysis - Nurul Hafizah; Shahilla Nur Fadhila; Muhamad Yahya; Muhammad Faiz; Sasmi Nelwati (Muaddib: Journal of Islamic Teaching and Learning, 2025)
The global phenomenon of moral degradation underscores the urgency of moral education as the foundation for shaping Muslim personality. In this context, Ibnu Miskawaih’s thought on tazkiyat al-nafs and ethics in his classical work Tahdzib al-Akhlak is highly relevant for Islamic character education in the modern era. Using a qualitative descriptive-analytical approach with content analysis, this study examines Tahdzib al-Akhlak as the primary source and compares it with contemporary literature. The results reveal four findings: first, Ibnu Miskawaih’s concept of soul balance nafs (desire), ‘aql (reason), and ghadab (anger) forms a systematic framework for cultivating virtues such as wisdom, courage, temperance, and justice. Second, this framework remains relevant in addressing extremism, hedonism, and moral decline, offering a middle path consistent with Quranic moderation and modern character education theories. Third, the concept has practical implications for curriculum and pedagogy, encouraging holistic education that integrates intellectual, emotional, and spiritual growth with teachers as role models. Fourth, Ibnu Miskawaih’s philosophy contributes to global moral discourse by providing a classical yet adaptable model for building ethical, inclusive, and sustainable societies. The novelty lies in reconstructing his thought as a practical educational model bridging classical Islamic wisdom with contemporary pedagogical needs.